Um estudo sobre o conteúdo descritivo na interpretação da obra "Quadros de Uma Exposição" de: Mussorgsky - Reale, Diva Evelyn (1992)
Study on the descriptive contents in the composition 'Pictures at an Exhibition' of Modest Mussorgsky, tries to give prominence to the importance, to the interpreter, of understanding the descriptive contents of this musical composition which covers, amongst other aspects, the source of inspiration of the composition, the pychological contents by the composer and the social influences, the history and "Russian Folclore". The work had, as a point of reference, the "Fac-simile" of the musical composition which made possible, the comparative study between the original and the various editions. In the research, there is a phonographic selection with observations as to the interpretative conception of important pianists. The biographic and stylistic contents were researched as also the influences and preferences of Mussorgsky. The author of the work, also, made two analyses of the composition, one of them being on the original pianistic version os "Pictures at an Exhibition" and the other on the orchestration of Ravel, identifying the composition procedures utilized by Mussorgsky to elaborate an essentially realistic and descriptive composition. Amongst the enclosures, may be found the "Fac-simile", the Urtex Edition Schott-Wien score, two analyses of the composition, an interview and photos.